Coherent pulse propagation in mid-infrared quantum-cascade lasers with nonlinear dispersive gain medium - Bai, Jing (2019)
Effects of group-velocity dispersion and self-phase modulation on coherent pulse progression in mid-infrared quantum-cascade lasers are investigated. The interaction between them is evaluated toward the soliton formation in the lasing cavity.